Maximum Utilization of Dynamic Rating Operated Distribution Transformer (DRoDT) with Battery Energy Storage System: Analysis on Impact from Battery Electric Vehicles Charging - Talpur, S; Lie, TT; Zamora, Ramon; Das, BP (MDPI AG, 2020)
This paper investigates thermal overloading, voltage dips and insulation failure across a distribution transformer (DT), under residential and battery electric vehicle (BEV) loadings. The objective of this paper is to discuss the charging impact of BEVs on voltage across consumer-service points, as well as across the life of paper insulation under varying ambient temperatures (during winter and summer), with and without a centralized battery energy storage system (BESS). This study contributes in two ways. The first part of this study deals with coordinated and uncoordinated BEV charging scenarios. The second part of this study deals with maximum utilization of a test DT rated under dynamic thermal rating (DRoDT). The DRoDT integration with BESS is carried out to flatten the load spikes, to obtain maximum DT utilization, to achieve active power and voltage supports in addition to an enhanced DT lifespan. The obtained results indicate that, when test DT operates under the proposed hybrid technique (combining both dynamic transformer ratings and a centralized BESS), it attains maximum utilization, lower hot-spot temperature, enhanced lifespan, less degraded paper insulation and an improved voltage across each consumer service point. The proposed technique is furthermore found effective in maintaining the loading across the distribution transformer within the nominal limits. However, under excess loading during peak hours, the proposed technique provides relief to the DT to a certain extent. To achieve an optimal DT operation and an enhanced BESS lifespan, the BESS is operated under nominal charging and discharging cyclic limits. Under the proposed DRoDT integration with BESS, DT attains 25.9% more life when loaded with coordinated BEV charging, in comparison to no BESS integration under the same loading scenario. The worst loading due to uncoordinated BEV charging also brings 51% increase in DT life when loaded under the proposed technique.
Keywords: Battery energy storage system; Coordinated versus uncoordinated battery electric vehicles charging; Distribution transformer; Dynamic transformer rating; Paper insulation